Toward International Standard: The Role of Village Tourism Awareness Group in Homestay Development of Kemiren Village - Mbulu, Yustisia Pasfatima; Gunadi, I Made Adhi (Journal of Business on Hospitality and Tourism, 2020)
This research aims to analyze the role of Pokdarwis in homestay development, analyze the quality of the homestay with the ASEAN Homestay Standard criteria, and analyze challenges and opportunities in developing a homestay. The method used is descriptive qualitative, with data collection techniques through observation and direct interviews. This study also conducted FGDs with homestay owners, the Head of the Kemiren Traditional Village, Pokdarwis, the Head of Kemiren Village, Banyuwangi Disbudpar, Dancers, PKK, and NGOs. The result of this research is the role of Pokdarwis as a Motivator, Communicator, and Driving Force. The quality of a homestay meets elements of the criteria of the host, activities, location, marketing & promotion, and sustainability principles. Meanwhile, elements of Safety & Security Criteria, Management, Accommodation, Cleanliness & Cleanliness still need to be improved. Challenges in terms of marketing & promotion, management, cleanliness & hygiene, and security & safety still need to be improved. The opportunity is enormous because it has all aspects to meet the accommodation standards of ASEAN-Class Homestay.